Pengaruh Brand Image dan Social Influence Terhadap Keputusan Pembelian Motor Matic Honda Vario - Suyanto Suyanto (Yos Soedarso Economic Journal (YEJ), 2024)
This research aims to determine the influence of independent variables (brand image and social influence) on the dependent variable (purchasing decisions). The population in this study were consumers of the Honda Dwitara Surabaya Dealer who use or have used Honda Vario motorbikes. The sampling technique uses the Probability Sampling method, namely a sampling technique that provides an equal opportunity for each element (member) of the population to be selected as a sample, the sample size is 50 people. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used is multiple linear regression. The results of the research show that: (1) Brand Image has a partial effect on Purchasing Decisions proven with a significant level of less than 0.05 (0.010 ≤ 0.05), (2) Social Influence has no partial effect on Purchasing Decisions proven with a significant level of more of 0.05 (0.175> 0.05) and, (3) Brand Image and Social Influence have a simultaneous influence on Purchasing Decisions, proven at a significant level of less than 0.05 (0.000 ≤ 0.05).